Pengaruh Komunikasi Kerja, Kompetensi, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT Indo Putra Harapan Sukses Makmur - Edward Raju Krisna Maulana; Kukuh Harianto; Suseno Hendratmoko (Master Manajemen, 2025)
This research aims to determine the influence of work communication, competence, work discipline and job satisfaction on employee performance. This type of research is quantitative research. This research data was obtained through primary and secondary data. The population in this study were 36 employees of PT Indo Putra Harapan Sukses. The sample in this study was 36 employees with a sampling technique using saturated sampling. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that the results of the t test partially show the variables of communication, competence, work discipline and job satisfaction on the performance of PT Indo Putra Harapan Sukses Makmur employees. Simultaneous F test results of communication, competency, work discipline and job satisfaction on the performance of PT Indo Putra Harapan Sukses Makmur employees